2008
DOI: 10.1152/ajplung.90207.2008
|View full text |Cite
|
Sign up to set email alerts
|

The role of caveolin-1 in pulmonary matrix remodeling and mechanical properties

Abstract: Caveolin-1 (cav1) is a 22-kDa membrane protein essential to the formation of small invaginations in the plasma membrane, called caveolae. The cav1 gene is expressed primarily in adherent cells such as endothelial and smooth muscle cells and fibroblasts. Caveolae contain a variety of signaling receptors, and cav1 notably downregulates transforming growth factor (TGF)-β signal transduction. In pulmonary pathologies such as interstitial fibrosis or emphysema, altered mechanical properties of the lungs are often a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 52 publications
4
42
0
Order By: Relevance
“…While much of the focus in the literature has centered on the importance of collagen to fi brosis, 21 it is possible that smaller ECM-connecting proteins, 22 like fi bulin-1 which binds to elastic fi bers, 12 can also act to alter the mechanical properties of the lung. 23 In this study, as the levels of tissue fi bulin-1 increased, the lung function of the patients decreased. Given that fi bulin-1 is a known modulator of the ECM during the progression of some diseases, 24 this fi nding is indicative of the potential importance of fi bulin-1 as a target during fi brogenesis.…”
Section: Discussionmentioning
confidence: 53%
“…While much of the focus in the literature has centered on the importance of collagen to fi brosis, 21 it is possible that smaller ECM-connecting proteins, 22 like fi bulin-1 which binds to elastic fi bers, 12 can also act to alter the mechanical properties of the lung. 23 In this study, as the levels of tissue fi bulin-1 increased, the lung function of the patients decreased. Given that fi bulin-1 is a known modulator of the ECM during the progression of some diseases, 24 this fi nding is indicative of the potential importance of fi bulin-1 as a target during fi brogenesis.…”
Section: Discussionmentioning
confidence: 53%
“…A single previous study that examined airway function in Cav1 KO mice (28) reported that, by 3 mo of age, lung compliance is significantly reduced whereas RL is increased. The reduced compliance was associated with increased deposition of collagen fibrils in the airways: a finding observed in the present study as well.…”
Section: Discussionmentioning
confidence: 98%
“…To this end we employed the mouse lacking caveolin-1 (Cav1 KO) as a model, with ovalbumin (OVA) sensitization and challenge as a model of allergic airway hyperresponsiveness to test our hypothesis. Cav1 KO mice are known to develop pulmonary fibrosis (9,15,60), and a single study showed that these mice have reduced lung compliance and increased elastance by 3 mo of age (28), with evidence of progressively greater deposition of collagen within airways and parenchyma. Whether such changes are associated with altered airway contractility and the specific role of ASM per se have not been examined.…”
mentioning
confidence: 99%
“…Numerous studies have supported this role of caveolin-1 in the development of tissue fibrosis [65][66][67][68]. For example, it was shown that caveolin-1 knockdown in vitro markedly increased collagen gene expression in normal human lung fibroblasts and that caveolin-1 was reduced in affected SSc lungs and skin [66] and in lung tissues and fibroblasts from patients with idiopathic pulmonary fibrosis [67,68]. Increasing caveolin-1 expression markedly improved bleomycin-induced pulmonary fibrosis [67].…”
Section: Protein Kinase C-δ (Pkc-δ) Pkc-δ Ismentioning
confidence: 94%
“…The localization of the TβRs in the EEA-1 positive compartment was responsible for downstream Smad activation, whereas their localization in caveolae lipid rafts caused recruitment of Smurf/Smad7 with subsequent receptor ubiquitination and rapid receptor degradation and turnover [63,64]. Numerous studies have supported this role of caveolin-1 in the development of tissue fibrosis [65][66][67][68]. For example, it was shown that caveolin-1 knockdown in vitro markedly increased collagen gene expression in normal human lung fibroblasts and that caveolin-1 was reduced in affected SSc lungs and skin [66] and in lung tissues and fibroblasts from patients with idiopathic pulmonary fibrosis [67,68].…”
Section: Protein Kinase C-δ (Pkc-δ) Pkc-δ Ismentioning
confidence: 99%